Worsening mental health of elderly people in front of COVID-19 (Research, Society and Development, 2021)
The new coronavirus responsible for the infectious disease called COVID-19 potentially affects risk groups with comorbidities, such as the elderly. The present study aimed to verify the impact caused by the COVID-19 pandemic on the mental health of elderly adults. Methodology: The systematic review followed the recommendations of the Preferred Reporting Items for Systematic Reviews and PRISMA Meta-Analyses (Moher et al., 2009). The search for articles was carried out in the Pepsic, Pubmed, Science Direct, Gerontology and Scielo databases. Data selection sought to systematize information on study objectives, methodology used, population studied and results achieved. Results: 408 articles were located, 12 were selected, nine of national origin and three foreign. The effects of the pandemic were related to isolation and social distancing and evidenced in symptoms of anxiety, depression, stress, changes in sleep and eating, among others. Conclusion: In view of the COVID-19 pandemic and its effects, providing transdisciplinary collective psychosocial support services, online, and paying attention to signs of damage to mental health and general health conditions of elderly adults, are public health measures priority.